Data-Independent Acquisition Proteomics Unravels the Effects of Iron Ions on Coronatine Synthesis in Pseudomonas syringae pv. tomato DC3000 - He, Yan; Yu, Sha; Liu, Shaojin; Tian, Hao; Yu, Chunxin; Tan, Weiming; Zhang, Jie; Li, Zhaohu; Jiang, Feng; Duan, Liusheng (Frontiers in Microbiology, 2020)
Coronatine (COR) is a new type of plant growth regulator that is produced by Pseudomonas syringae pathovars and plays an important role in modulating plant growth, development, and tolerance to multiple stresses, but the factors affecting coronatine production are not very clear. In this study, the effects of FeCl3 on the yield of coronatine was researched and the independent data acquisition (DIA) approach, which is a proteomic quantitative analysis method, was applied to quantitatively trace coronatine production and proteomic changes in Pseudomonas syringae pv. tomato DC3000 under different FeCl3 culture conditions. The results showed that coronatine production increased with the addition of FeCl3, and that there was significant upregulation in the expression of proteins related to coronatine synthesis and regulation. In addition, FeCl3 also affected the expression of related proteins involved in various metabolic pathways such as glycolysis and the tricarboxylic acid (TCA) cycle. Moreover, various precursors such as isoleucine and succinate semialdehyde, as well as other related proteins involved in the coronatine synthesis pathway were significantly differentially expressed. Our findings revealed the dynamic regulation of coronatine production by FeCl3 at the protein level, and proved the potential of using the DIA method to track the dynamic changes of the Pseudomonas syringae pv. tomato DC3000 proteome during coronatine production, providing an important reference for future research on the regulatory mechanism of coronatine biosynthesis and theoretical support for coronatine fermentation production.